Intra-oral intramuscular lipoma in a child masquerading as plunging ranula diagnosed on cytology - Dhammi, Sarvesh; Bhargav, Mithlesh; Gopal, Vaibhav Raj (International Journal of Research in Medical Sciences, 2026)
Intra-oral intramuscular lipomas are rare, especially in pediatric populations. Their clinical presentation may mimic more common cystic lesions such as plunging ranulas, often leading to diagnostic confusion. We reported a rare case of an intramuscular lipoma of the floor of the mouth in a child, initially suspected to be a plunging ranula due to its submandibular swelling and soft, fluctuant consistency. Fine needle aspiration cytology (FNAC) revealed mature adipocytes without cystic or inflammatory elements, confirming the diagnosis of intramuscular lipoma. Surgical excision was performed, and histopathology corroborated the cytological findings. This case highlights the diagnostic challenge posed by intramuscular lipomas in the oral cavity of children and underscores the critical role of FNAC in distinguishing them from more common cystic lesions like plunging ranulas. Early and accurate diagnosis is essential to guide appropriate surgical management and prevent recurrence.